Λ-Bernstein Operators Based on Pólya Distribution. (26th April 2023) - Lipi, Km.; Deo, Naokant
Abstract: In this manuscript, we propose a Pólya distribution-based generalization of λ -Bernstein operators. We establish some fundamental results for convergence as well as order of approximation of the proposed operators. We present theoretical result and graph to demonstrate the proposed operator's intriguing ability to interpolate at the interval's end points. In order to illustrate the convergence of proposed operators as well as the effect of changing the parameter " μ, " we provide a variety of results and graphs as our paper's conclusion.